ANALISIS PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA YARIS DI KECAMATAN PANCORAN MAS, DEPOK - Fadilla Rakhmanisa, - (2019)
This research is a quantitative research which aims to determine the analysis of the effect of the promotion mix on Buying decisions. The population in this study was the community of Depok Pancoran mas District. The sample size was taken as many as 60 respondents, with a non probability sampling method especially purposive sampling. Data collection is done through questionnaires.The analysis technique used is the method of PLS (Partial Least Square) analysis.The results of this study indicate that (1) advertising does not have a significant effect on buying decision with path coficient values of 0.082. (2) sales promotion has a significant influence on the buying decision with a path coefficient of 0.108. (3) public relations does not have a significant influence on buying decision with a path coefficient of -0,017. (4) personal selling significant effect on buying decision with path coefficient values of 0,456. (5) direct marketing has a significant influence on buying decision with a coefficient path value of 0.427.